2008
DOI: 10.1093/aje/kwn234
|View full text |Cite
|
Sign up to set email alerts
|

Spousal Concordance for Major Coronary Risk Factors: A Systematic Review and Meta-Analysis

Abstract: Spousal pairs permit assessment of determinants of diseases related to environment, because they share the same lifestyle and environment. The authors reviewed spouses' concordance for the major coronary risk factors. A search of the MEDLINE, PubMed, and EMBASE databases was performed. Seventy-one papers were selected for a total of 207 cohorts of pairs and 424,613 correlations in more than 100,000 couples. The most strongly correlated within-pairs factors were smoking and body mass index, with overall correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
199
4
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(236 citation statements)
references
References 66 publications
30
199
4
3
Order By: Relevance
“…Pregnancy is 'a time when science and society diverge on the topic of weight' (Kraschnewski 2014 e257) and, as the accounts here demonstrate, there exist deeply ingrained beliefs regarding food and nutrition in pregnancy, such as the benefits of following cravings, the need to increase intake of certain foods and the inevitability of weight gain. It has been observed that people on average gain weight in married and cohabitating relationships (Averett et al, 2008), and that there is a tendency for couples' BMIs to correlate (Jacobson et al, 2007;Di Castelnuovo et al, 2009). There are currently no UK guidelines regarding healthy weight gain in pregnancy (NICE, 2010), and a recent review of interventions concluded that 'there remains no evidence-based approach for any specific dietary regimen to improve pregnancy outcome in overweight and obese women' (Flynn et al, 2016 p326).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy is 'a time when science and society diverge on the topic of weight' (Kraschnewski 2014 e257) and, as the accounts here demonstrate, there exist deeply ingrained beliefs regarding food and nutrition in pregnancy, such as the benefits of following cravings, the need to increase intake of certain foods and the inevitability of weight gain. It has been observed that people on average gain weight in married and cohabitating relationships (Averett et al, 2008), and that there is a tendency for couples' BMIs to correlate (Jacobson et al, 2007;Di Castelnuovo et al, 2009). There are currently no UK guidelines regarding healthy weight gain in pregnancy (NICE, 2010), and a recent review of interventions concluded that 'there remains no evidence-based approach for any specific dietary regimen to improve pregnancy outcome in overweight and obese women' (Flynn et al, 2016 p326).…”
Section: Discussionmentioning
confidence: 99%
“…Central obesity was not measured in their study [39]. Di Castelnuovo and his team through a metaanalysis on spousal concordance for cardiovascular risk factors state that very few studies have investigated spousal concordance for such risk factors as the metabolic syndrome, and more data was required for meaningful analysis [40]. Leong et al conducted a systematic review and meta-analysis to examine spousal association for diabetes.…”
Section: B)mentioning
confidence: 99%
“…Studies in the UK have identified the characteristics of supplement users (SU) and found that SU are more likely to have a normal weight, a higher social class and show more health-conscious behaviours (3)(4)(5) . They have focused on the SU as an individual; however, people sharing a household could influence each other's behaviour, as has been shown for other types of behaviours such as smoking (6) . Concordance in the choice of using a supplement might partly explain why not all SU consistently show healthy behaviours; their spouse might have influenced them without the SU showing the known characteristics of a SU.…”
Section: Dietary Supplement Concordance Spouse Sociodemographic Variamentioning
confidence: 99%